2016
DOI: 10.1007/s40520-016-0553-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor cognitive status among older Malaysian adults: baseline findings from the LRGS TUA cohort study

Abstract: This study will be a stepping stone for future researchers to develop intervention strategies to prevent cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 33 publications
1
42
1
1
Order By: Relevance
“…Among aging Malaysian men, caloric restriction for three months resulted in body weight and fat loss, alleviated depression, and improved quality of life [ 32 ]. A large community-based cohort study involving 1993 older Malaysian adults showed that not practicing calorie restriction was a risk factor for poor cognitive performance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among aging Malaysian men, caloric restriction for three months resulted in body weight and fat loss, alleviated depression, and improved quality of life [ 32 ]. A large community-based cohort study involving 1993 older Malaysian adults showed that not practicing calorie restriction was a risk factor for poor cognitive performance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The website content was based on the data gathered from the study of literature and the outcome from the evaluation of the first phase of the research. 19 …”
Section: Methodsmentioning
confidence: 99%
“…These 10 suggestions were obtained from reviews of previous literature and a local demonstrative study performed among 1993 Malaysian older people for discovering risk factors regarding cognitive impairment ( Figure 2 shows the UI of the 10 guides for memory enhancement). 19 …”
Section: Methodsmentioning
confidence: 99%
“…Amongst the Malaysian community dwelling older population, the prevalence of frailty and pre-frailty was reported to be 8.9 and 61.7%, respectively (11), whereas MCI is prevalent at 16% (12). Prevalence of frailty and pre-frailty has been reported to be much higher amongst institutionalized older persons at 40.7 and 56.6%, respectively, with cognitive impairment as a predictor (13).…”
Section: Introductionmentioning
confidence: 99%